Rede neural não supervisionada baseada em transformada Karhunen-Loève para processamento, compressão e reconhecimento de imagens - Marar, João Fernando [UNESP]; De Barros Carvalho Filho, Edson Costa; Dos Santos, José Dias (My University, 1997)
The merit of the Karhunen-Loève transform is well known. Since its basis is the eigenvector set of the covariance matrix, a statistical, not functional, representation of the variance in pattern ensembles is generated. By using the Karhunen-Loève transform coefficients as a natural feature representation of a character image, the eigenvector set can be regarded as an feature extractor for a classifier.
Keywords: Karhunen-Loève Transform; Neural Networks; Pattern Recognition